Metagenomics-guided targeted isolation and mechanistic elucidation of haloalkaliphilic bisphenol A-degrading microorganisms - Sai Yang; Kai-yan Xing; Yue-fei Tao; Jia-yu Wang; Ke-hang Liu; Meng Zhang; Xiang-ru Xu; Lin Zhu; Wei Wei (Bioresource Technology, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

A novel fungus Penicillium crocicola LF-2022 for high-efficiency biodegradation of brominated flame retardants: Performance, pathways, soil remediation, and transcriptomic mechanisms - Yan Li; Ruiying Wu; Zhenglin Xia; Zhinan Jiang; Haitao Wu; Chen Lin; Jiaqing Chen; Fei Li (Journal of Hazardous Materials, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Numerical investigation with viscosity of nonlinear wave forces on a dual-tube submerged floating tunnel - Hong-fei Mao; Kai-lin Chen; Long Han; Zhong-bing Zhou; Yan-li He; Li-min Wang; Jing Xie (Ocean Engineering, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Aging-Related Changes in the Injury Response of the Peripheral Nervous System - Yue-Yan Cen; Mu-Yun Wang; Qin-Xuan Song; Xin-Lin Gao; Cheng Zhou; Chun-Jie Li; Fei Liu; Yan-Yan Zhang; Jie-Fei Shen (Neuroscience Bulletin, 2026)
Peripheral nerve injury (PNI) significantly impairs patients’ quality of life, with elderly individuals experiencing particularly severe consequences due to aging-related declines in neuronal injury response and repair capabilities. Processes of the generation and transmission of injury signals, axonal disruption, initiation of regeneration, and the elongation of regenerating axons, as well as the subsequent reinnervation by these axons, are all significantly influenced by aging. These alterations are closely associated with changes in mitochondrial function, neuronal transport systems, a persistent inflammatory milieu, and various microenvironmental non-neuronal cells. Therefore, this review synthesized the pivotal role of aging in the multifaceted regulation of the nervous system following PNI and highlighted promising molecular regulatory mechanisms in the signaling pathways. Furthermore, it identified critical areas for future research, including unresolved questions in age-associated injury responses, potential targets for pharmacological intervention, and emerging therapeutic strategies meriting consideration for research and development.

Salidroside Alleviates Mobocertinib-Induced Cardiotoxicity by Improving Cardiac Electrophysiology - Chi Yan; Xiaohong Liu; Xiaoyan Zhang; Pei Wei; Xuefang Li; Dongxu Li; Guhao Zhang; Meng Li; Xiayan Zang; Guangjian Lu; Fei Lin (Cardiovascular Toxicology, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

Estuaries as fragmentation hotspots and transport regulators of microplastics - Yancheng Lv; Fei Jiang; Yihe Wang; Yuye Chen; Yan Yang; Jinyang Lin; Xiaoteng Shen; Qiqing Chen (Marine Pollution Bulletin, 2026)

Mean warming enhances insect resilience to high temperatures: species-specific evidence from two wheat aphids - Xue-Jing Wang; Yu Wang; Shu-Lin Ning; Jia-Qi Li; Biao Cui; Long-Fei Yue; Li-Yan Wang; Chun-Sen Ma (Journal of Insect Physiology, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Revealing the kinetic promotion mechanism of carbon nanotubes to methane hydrate formation: As to the situation coupled with traditional kinetic promoter L-leucine - Yan Lin; Yan-Ling Guo; Zhi-Yuan Wang; Jie Zhong; Xiao-Ming Wang; Yi-Ning Ding; Hong-Zheng Lu; Fei Wang; Xiao-Lin Wang (Chemical Engineering Journal, 2026)

CAMP-negative group B Streptococcus in pregnant women: molecular and clinical features with implications for diagnostics and neonatal management - Lianfen Huang; Zeying Lin; Sufei Zhu; Chengman Fong; Zengyu Tan; Kankan Gao; Manqiu Kang; Zimeng Liu; Xiaolan Chen; Huamin Zhong; Yongqiang Xie; Bingshao Liang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Pseudostellaria heterophylla Extract Enhances the Immune Responses in Larimichthys crocea Against Pseudomonas plecoglossicida Infection - Kun Huang Han; Zi Min Li; Li Zhou; Dong Ling Zhang; Ying Li; Zhao Han Sun; Jia Chen; Zhi Deng Lin; Yan Bin Dai; Peng Fei Zou (Fishes, 2026)
Visceral white spot disease caused by Pseudomonas plecoglossicida poses a severe threat to large yellow croaker (Larimichthys crocea) aquaculture. This study investigated the immunomodulatory effects and underlying mechanisms of Pseudostellaria heterophylla extract against P. plecoglossicida infection in L. crocea. Fish were fed a basal diet supplemented with 1% P. heterophylla extract for 30, 45, and 60 days, followed by intraperitoneal injection with 200 μL P. plecoglossicida (1 × 104 CFU/mL). When the control group reached about 50% mortality, transcriptome sequencing of head kidney tissues was performed on the 45 and 60 days post-feeding of the treatment groups to analyze gene expression changes following bacterial infection. Survival rates of the treatment groups were 33.33%, 13.33%, and 20% higher than those of the control group at 30, 45, and 60 days post-feeding, respectively. Transcriptomic analysis revealed time-dependent transcriptional responses: in one group, 45 days post-feeding, 10 differentially expressed genes (DEGs) were identified (2 up-regulated and 8 down-regulated), whereas in another group, 60 days post-feeding, 893 DEGs were detected (417 up-regulated and 476 down-regulated). Functional enrichment analysis (GO, KEGG, and GSEA) demonstrated that DEGs were significantly enriched in immune-related pathways, including Toll-like receptor signaling, chemokine activity, Th1 and Th2 cell differentiation, hematopoietic cell lineage, and cytokine–cytokine receptor interaction. Key immune genes, including chemokines, Toll-like receptors, and T cell regulators, were significantly up-regulated. These findings indicate that P. heterophylla extract enhances both the specific and non-specific immune capabilities of L. crocea in a time-dependent manner, with prolonged supplementation eliciting more robust transcriptional activation of immune defense pathways. This study provides a scientific foundation for developing immunological prevention strategies against P. plecoglossicida infection in aquaculture.

Time-Series Transcriptomics of a Gill Cell Line (BTG) from Chinese Bahaba (Bahaba taipingensis) During ISKNV Infection (3–24 hpi) - Chenfei Guo; Zhihong Gong; Fei Fang; Xihong Li; Lei Wang; Na Wang; Zhangfan Chen; Lin Yan; Kuoqiu Yan; Guobin Hu; Songlin Chen (Fishes, 2026)
The Chinese bahaba (Bahaba taipingensis), an endangered marine fish, is highly vulnerable to infectious spleen and kidney necrosis virus (ISKNV). In this work, we developed a gill filament-derived cell line, designated BTG, to investigate how these cells respond to ISKNV over time, specifically from 3 to 24 h post-infection (hpi). BTG cells grew steadily, displayed a diploid chromosome number of 2n = 48, demonstrated high transfection efficiency, and were highly susceptible to viral infection. Characteristic cytopathic effects (CPEs) became noticeable as early as 6 hpi at 27 °C. RNA-seq profiling showed that the number of differentially expressed genes (DEGs) steadily increased with time. Standard enrichment analysis at individual time points (3, 6, 12, and 24 hpi) highlighted pathways mainly involved in DNA replication, cell cycle control, ribosome assembly, transcription and translation, mismatch repair, and cell adhesion. Temporal clustering analysis, however, revealed hidden patterns in immune gene expression. Genes that were consistently downregulated were enriched in immune-related pathways, including ECM–receptor interaction, cytokine–receptor signaling, PI3K–AKT, and Wnt signaling, indicating prolonged suppression of host defense mechanisms. In contrast, clusters of genes transiently upregulated during the first 6 h post-infection were associated with antiviral and innate immune pathways, such as NF-κB, JNK, IRF3, IRF7, caspases, JAK, MHC I, and lysosome-related functions, suggesting a rapid but short-lived antiviral response. Genes that were continuously upregulated were primarily involved in nucleic acid replication and protein synthesis, reflecting a gradual host cell reprogramming to support viral replication. Taken together, these findings reveal a temporal shift in BTG cells from an initial burst of immune activity to immune suppression, accompanied by enhanced viral replication. The BTG cell line thus represents a valuable in vitro model for dissecting ISKNV–host interactions and offers new perspectives on the molecular strategies employed by megalocytiviruses in B. taipingensis.

Effects of inoculum sources from different depths and oxygen concentration on bioleaching and microbial community assembly in mine waste dump - Zi Han Lin; Bing Zhou; Chen Sheng Zhang; Xuan Qi Zhang; Yan Bo Chen; Min Liang Fei; Xiao Fei Wei; Zhang Zheng Cai; Tian Shou Hu; Jie Hu; Han Ke (Journal of Hazardous Materials, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

The rising power of females: Dioecious shrub enhances soil organic carbon sequestration via fungal necromass in chronosequence of desertified alpine grassland restoration - Dongming Chen; Muhammad Ibrar; Fei Yan; Geng Sun; Ran Xue; Aomei Jia; Jiqiong Zhou; Yongheng Gao; Congyu Ma; Meng Wang; Jian Zhang; Zhouwen Ma; et al. (Journal of Environmental Management, 2026)

Compositional profiling and inter-cultivar variation of flavonoids in some red table grapes cultivated in China: Assessing the quality-indicative potential of anthocyanins, flavonols, and flavanols - Shang-Lin Wang; Hai-Bei Yan; Lin Wang; Xing-Chi Chen; Jun Wang; Fei He (Food Chemistry, 2026)

Different land use types around megacities contribute contrasting heavy metal pollution and health risks in soil-leaf vegetable systems - Ling Huang; Wen-Fei Chen; Yue-E Guan; Yan-Ping Pang; Sheng-Gong Yu; Lin Li; Qi Zou; Meng-Qiang Sun; Hang Wei; Zhi-Liang Chen (Environmental Research, 2026)

Retraction notice to “Cost-effective fabrication of fluorite tailings-based calcium silicate hydrate for excellent adsorption performance of Cr (III) from aqueous solution” [Environ. Res. 285 (2025) 122318] - Pengfei Zhou; Xianku Wang; Mingyang Qi; Hairui Yao; Yan Shi; Lin Hao; Jinsheng Liang; Richard M. Laine; Fei Wang (Environmental Research, 2026)

Genetic regulation of insulin resistance surrogate index (TyG) and susceptibility to common diseases based on phenome-wide association study - Jia-Xin Wu; Ling-Huan Bu; Pei He; Ming-Hui Xia; Lin Bo; Fei-Yan Deng; Shu-Feng Lei (Molecular and Cellular Biochemistry, 2026)

Enhanced cycling and thermal stability of nickel-rich cathodes for lithium-ion batteries via molecular-weight-tuned polyaniline–polyethylene glycol interphase - Lin-Jie Xie; Jun-Cheng Jiang; Chen Liang; Qing-Song Wang; Hui-Qi Sun; Yan Tang; An-Chi Huang; Fei-Hao Zhu; Chi-Min Shu (Process Safety and Environmental Protection, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

CuI additive induced co-regulation of ion transport and interfacial chemistry in poly(ethylene oxide)-based solid-state electrolytes for improved battery performance - Kepan Yan; Xuexiao Chen; Haoliang Huang; Zicong Yu; Jingcheng Lu; Zhipeng Yu; Sitaramanjaneya Mouli Thalluri; Jinfeng Zeng; Wei Wang; Fei Lin; Yijuan Li; Weicai Zhang; et al. (Chemical Engineering Journal, 2026)

Exploration of salivary biomarkers for accurate diagnosis of anxiety, depression, and somatic symptom disorder by the integration of microfluidic chip and machine learning - Rongjie Wang; Fei Xu; Lin Wang; Xue Zhang; Miao Huang; Zhun Wei; Yan Jiang; Yunhong Zhang; Xiaoshuang Chen; Yanbo Liang; Yu Zhang; Xueqin Mao; et al. (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Comparing the performance of different hyperspectral satellite imaging spectroscopy in mapping methane point-source emissions - Fei Li; Keer Lin; Yingqi Yan; Shengxi Bai; Qidan Huang; Chenxi Feng; Shiwei Sun; Shaohua Zhao; Wei Zhou; Chunyan Zhou; Jun Lin; Xinwei Zhang; et al. (Remote Sensing of Environment, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

Autumnicola aciditolerans sp. nov., a novel member of the genus Autumnicola isolated from tidal flat in Zhoushan - Yang Li; Dong-Yan He; Jia-Wei Gao; Ke Cao; Yun-Fei Cao; Xing-Cheng Wang; Lin Xu; Yan Bai; Can Chen; Cong Sun (Antonie van Leeuwenhoek, 2026)

Inhibitory activity and antifungal mechanism of venturicidin A against Pyricularia oryzae - Yinan Wang; Lin Qi; Fei Liu; Chentong Yan; Fuqiang Zhao; Zhiguo Yu (Pesticide Biochemistry and Physiology, 2026)

RSK2 facilitates beige fat formation through thermogenic and glycolytic pathways - Yan Cai; Jun-jun Chen; Lin-fei He; Yao Xu; Rui-qi Yang; Zhi-chun Yang (Journal of Thermal Biology, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Molecular characterization of a novel partitivirus from quinoa (Chenopodium quinoa) in China - Wenqi Mao; Jiajia Lin; Zhongtian Xu; Penghuan Rui; Xinxin Fang; Hongying Zheng; Yuwen Lu; Jianping Chen; Fei Yan; Guanwei Wu (Archives of Virology, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Enhancing capacitive energy storage in Na0.5Bi0.5TiO3-based relaxor ferroelectric ceramics by tuning polymorphic polar nanoregions - Binglong Zheng; Ying Lin; Fei Yan; Qibin Yuan; Yongzhen Ma; Yanlong Ma; Yu Zhang; Da Li; Haibo Yang (Chemical Engineering Journal, 2026)

Acoustic manipulation and intracellular drug release promote bone marrow mesenchymal stem cells to repair articular cartilage defect - Panhui Huang; Qiong Luo; Lin Yao; Zhuqing Song; Jieqiong Wang; Shaolin Li; Fei Yan (Chemical Engineering Journal, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Fracture influence on karst development in carbonate reservoirs: Insights from the Lichuan karst region, Hubei, China - Hadi Hussain; Lu Yun; Fei Cao; Min Yang; Yan Wang; Xinhua Li; Lin Pan; Xiao Wang; Wakeel Hussain; Faulo James (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

RETRACTED: Cost-effective fabrication of fluorite tailings-based calcium silicate hydrate for excellent adsorption performance of Cr (III) from aqueous solution - Pengfei Zhou; Xianku Wang; Mingyang Qi; Hairui Yao; Yan Shi; Lin Hao; Jinsheng Liang; Richard M. Laine; Fei Wang (Environmental Research, 2025)

The Double-Edged Effect of Connexins and Pannexins of Glial Cells in Central and Peripheral Nervous System After Nerve Injury - Yue-Yan Cen; Xin-Lin Gao; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen; Yan-Yan Zhang (Molecular Neurobiology, 2025)

Identification of CaMATE genes family in pepper and functional characterization of CaMATE27 in capsaicin accumulation - Liuying Fei; Rahat Sharif; Wanming Yan; Lin Chen; Yi Liao; Zhangsheng Zhu; Guoju Chen; Changming Chen (Plant Science, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Contrasting impacts of grassland restoration methods on soil greenhouse gases emissions under warming conditions in Northern Tibet - Hao Shi; Fei Xia; Lin-ling Ran; Hao-yang Wu; Jun-qiang Wang; Yun-yin Xue; Wei Wei; Shai-kun Zheng; Shuang Yan; Cai-hong Yang; Yu Zhang; Xiao-qin Qiu (CATENA, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Identification of heavy metal transport-related genes and microRNAs in response to cadmium toxicity and micronutrient deficiency in barley roots - Liuhui Kuang; Jian Chen; Jie Ding; Tao Yan; Fei Gao; Lin Li; Zhigang Han; Dezhi Wu (Journal of Hazardous Materials, 2025)

Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Yan-Jun Bao; Yuan-Yuan Sun; Di Zhang; Jian-Fei Yan; Yu-Peng Men; Wei Sun; Jia-Shan Lin; You-Li Wan; Jian-Wei Kang; Wen-Hua Wang; Qiangba Zhaxi (Journal of Asian Earth Sciences, 2025)

Substrate cultivation system improved the quality of ‘Hongyan’ strawberry fruits compared with the soil cultivation system - Su Xu; Dajuan Shi; Haijiang Chen; Fengwei Ma; Guangcan Tao; Wenneng Wu; Dong Lin; Siyao Wu; Qiang Fei; Yan Hu; Lingshuai Meng (Food Chemistry, 2025)

Aurantibrevibacter litoralis gen. nov. sp. nov. a Novel Member in the Family Flavobacteriaceae Isolated from Sediment of Tidal Flat Located in Ningbo, China - Yun-Fei Cao; Dong-Yan He; Yu-Ruo Wang; Ke Cao; Yang Li; Jia-Wei Gao; Xing-Cheng Wang; Lin Xu; Cong Sun; Xiao-Yun Yu (Current Microbiology, 2025)

A new illudane sesquiterpene from the edible fungus Pholiota nameko - Lian Yang; Huan Zhang; Shu-Hang He; Ju Xu; Xiao-Long Li; Fei-Xing Li; Dong-Mei Lin; Deng-Ji Lou; Xiao-Yan Yang (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

Layered hydroxide-supported nano zero-valent iron via nanoarchitectonic design: Enhanced stability and degradation of fluorescent whitening agents - Fei Li; Chen Wang; Pingning Jin; Yaqi Lin; Yan Zheng; Jing Fan (Chemical Engineering Journal, 2025)

Recommendations of Stable Mg, Si, V, Fe, Cu, Zn, Rb, Sr, Ag, Cd, Ba, and U Isotope Compositions for Multiple Geological References - Jinting Kang; Xuqi Chen; Xi Deng; Yuan Fang; Haichuan Jiang; Chengyihong Liu; Cuihua Luo; Xing Li; Yuchao Lin; Zhaoqi Ren; Jiaru Sheng; Xue Tang; et al. (Journal of Earth Science, 2025)

Mitochondrial dysfunction and aging: multidimensional mechanisms and therapeutic strategies - Pei Wei; Xiaoyan Zhang; Chi Yan; Siyu Sun; Zhigang Chen; Fei Lin (Biogerontology, 2025)

The methods for the retrieval of land surface temperature in central Shijiazhuang using ASTER data - Biao Zeng; Guo-fei Shang; Xia Zhang; Ye-lin Shen; Yu-jia Tian; Zheng-hong Yan (Environmental Monitoring and Assessment, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Viscosity is a nonnegligible factor in the waste activated sludge fermentation: Taking hyaluronan as an example - Yan-Lin Hu; Kun Dai; Qing-Ting Wang; Chen-Yuan Zhou; Xing-Chen Huang; Xiao-Fei Yang; He-Liang Pang; Raymond Jianxiong Zeng; Fang Zhang (Water Research, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Molecular mechanisms based on peripheral level of vanillin recognition in Orthaga achatina (Lepidoptera: Pyralidae) - Ting-Ting Yang; Yu Ma; Zheng Dai; Ying Li; Ji-Xiang Wang; Teng-Fei Bai; Merid Negash Getahun; George F.O. Obiero; Shuang-Lin Dong; Jin Zhang; Qi Yan (Insect Biochemistry and Molecular Biology, 2025)

Root exudates of Salix cupularis orchestrate the accumulation of soil carbon and nitrogen in the rhizosphere during the restoration of a desertified alpine meadow - Qi Li; Fei Yan; Dongming Chen; Jiqiong Zhou; Zhouwen Ma; Yanfu Bai; Xingpeng Hu; Congyu Ma; Abeer S. Aloufi; Feida Sun; Anna Gunina; Jian Zhang; et al. (Applied Soil Ecology, 2025)

Organic fertilizer application reduce ammonia volatilization in an acidic soil - Cai Gan; Yanbin Jiang; Yan Wang; Shan Lin; Yue Luo; Huabin Li; Yunwei Li; Niannian Tang; Yang Fei; Ronggui Hu (Agriculture, Ecosystems & Environment, 2025)

Application of cryogenic grinding combined with ultrasonic pretreatment to enhance the yield and quality of essential oils from nutmeg (Myristica fragrans Houtt.) - Jiaming Yan; Sidan Zhao; Zhengyun Liang; Hanchen Lin; Ning Ma; Chaoqun You; Fei Wang (Sustainable Chemistry and Pharmacy, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

Ambient drying fabrication of mechanically robust, flame-retardant, thermal-insulating cellulose/aramid nanofiber composite foam via freeze-casting combined ion cross-linking - Zijing Liu; Xu Lin; Xueyan Mai; Jiandong Zhuang; Fei Guo; Rilong Yang; Yan Yu; Xuexia Zhang (Carbohydrate Polymers, 2025)

Structural and (U-Th)/He thermochronological constraints on the Longmen Shan thrusting-gliding klippes, eastern margin of Tibetan Plateau - Xiaohan Lin; Danping Yan; Liang Qiu; Zhicheng Zhou; Huajie Song; Fei Kong; Chao Du (Science China Earth Sciences, 2025)

Assessment of the growth and quality of pepper seedlings under the combinations of daily light integral and nitrogen concentration - Zhengnan Yan; Xiuxiu Cao; Lixue Bing; Duo Lin; Fei Cheng; Kaiyan Wang; Ye Qi; Yanjie Yang (Horticulture, Environment, and Biotechnology, 2025)

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

Retraction Note: A New Luminescent Zn(II) Complex: Selective Sensing of Cr2O72 − and Prevention Activity Against Orthodontic Root Absorption by Suppressing Inflammatory Response - Yan-Feng Zhu; Wei-Qun Guan; Fei Lin; Wei-Hui Chen (Journal of Fluorescence, 2025)

Mechanism of Epigallocatechin-3-gallate in the prevention and treatment of irritable bowel syndrome: A network pharmacology and gene expression omnibus chip data-based study - Fangchen Ye; Laifu Li; Lianli Wang; Yan Ran; Lin Mei; Yating Sun; Xinping Zhang; Fei Dai (PharmaNutrition, 2025)

Tillage effects on maize yield, N use efficiency and GHG emissions under parallel N application in Northwest China - Hao-yang Wu; Lin-ling Ran; Jun-qiang Wang; Shuang Yan; Yun-yin Xue; Fei Xia; Hao Shi; Wei Wei; Yu Zhang; Shai-kun Zheng (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

Outstanding comprehensive energy storage performance in BNT-based lead-free ceramics via synergistic optimization strategy - Zixin Li; Wenjie Zhou; Jinming Guo; Xinye Lv; Shuxin Lin; Yilang Li; Long Gu; Fei Yan (Chemical Engineering Journal, 2025)

Forms of rare earth loss and the function mechanism of acetic acid in the aluminum removal process of rare earth leaching liquor - Chen Xin; Chen Jin-fa; Xiao Xin-lei; Fan Lin; Xiao Yan-fei; Huang Li (Minerals Engineering, 2024)

Faulted karst reservoir spaces in Middle-Lower Triassic carbonates, Qingjiang Region, Yangtze block, China - Shixi Liao; Fei Cao; Lin Jiang; Yan Wang; Peijin Li; Chaohua Guo; Lin Pan; Xiao Wang (Journal of Structural Geology, 2024)

Lignanamides: A comprehensive review of chemical constituents, biological activities, extraction methods and synthetic pathway - Jing Sun; Li-Tao Tong; Peng-Fei Tu; Lin-Lin Chen; Xin Xu; Ya Song; Xin-Xin Yang; Zi-Bin Guo; Xiang Zou; Chen-Xin Sun; Yan Mi; Bei Fan; et al. (Food Chemistry, 2024)

Activated proton storage in molybdenum selenide via nanostructure molecular engineering - Fei Long; Long Zhang; Shuwen Yan; Yangwang Zhou; Xinying Lin; Luying Li; Yihua Gao (Chemical Engineering Journal, 2024)

Ultra-capacity and low-cost P3-type K0.5Mn0.96Fe0.04O2 cathode materials for K-ion batteries - Jun Cong; Shao-hua Luo; Yi-cheng Lin; Peng-yu Li; Li-xiong Qian; Sheng-xue Yan; Xin Liu; Xue-fei Lei (Chemical Engineering Journal, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

OsNAC15 regulates drought and salt tolerance in rice - Chuan-Wei Ao; Gan-ju Xiang; Yan-Fei Wu; Yue Wen; Zhong-Lin Zhu; Feng Sheng; Xuezhu Du (Physiology and Molecular Biology of Plants, 2024)

Global research trends in Rhizodeposition-mediated soil carbon cycle: A bibliometric analysis - Dongming Chen; Fei Yan; Xuemei Fang; Jiqiong Zhou; Xingpeng Hu; Xiaoming Ma; Xin Zheng; Rui Yin; Feida Sun; Yanfu Bai; Zhouwen Ma; Yakov Kuzyakov; et al. (Applied Soil Ecology, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

A high-entropy strategy for stable structure of sodium ion batteries: From fundamentals to applications - Xu Liu; Xin-Yu Liu; Nan Zhang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Jie Shu; Yan Sun; Chun-Sheng Li; Ting-Feng Yi (Chemical Engineering Journal, 2024)

High-performance static formation of methane hydrate in fixed bed constructed by incorporating expanded graphite into polyimide foam - Xinran Sun; Daiming Liu; Zhibing Xuan; Yongtao Zhang; Guodong Zhang; Chen Chen; Mengting Sun; Yan Lin; Jie Zhong; Fei Wang (Chemical Engineering Journal, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Correction to: The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2024)

Synthesis of two Fluorescent Complexes and Their use as Multifunctional Nanomedicine Carriers for Rhabdomyosarcoma Treatment - Ping Yang; Peng Xie; Feng Lin; Tian Wang; Lian Zhang; Fei Yan (Journal of Fluorescence, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Nonlinear elastic deformation model of belled uplift piles under the coupling effects of groundwater and shear strain relaxation - Yan-lin Li; Jian Lu; Aijun Yao; Hui Li; Yi-Fei Gong (Computers and Geotechnics, 2024)

Cu-based bubble and ion sieve for ampere-level hydrogen evolution - Si-Wei Yan; Chuan-Qi Cheng; Fei-Fei Zhang; Ze-Yu Zhang; Kui Lin; Peng-Fei Yin; Rui Zhang; Jing Yang; Cun-Ku Dong; Jing Mao; Hui Liu; Xi-Wen Du (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

Transcriptomic mechanism revealed IbGST4 and IbGST2 genes response to low-temperature stress in sweet potatoes - Wei-Sheng Zhao; Long-Fei Yan; Kang-Di Hu; Zhi-Lin Zhou; Si-Qi Wang; Le-Ying Yan; Fan Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

A microelectrode electrochemical sensing platform based on heteroatoms doped carbon nanotubes arrays with peroxidase-like activity for in-situ detection in live cell - Yan Zhang; Tao Lin; Minghui Han; Min Hu; Yun Xu; Wei Huang; Fei Xiao; Anshun Zhao (Analytica Chimica Acta, 2024)

Simultaneous determination of seawater trimethylamine and methanol by purge and trap gas chromatography using dual nitrogen-phosphorus detector and flame-ionization detector - Fei Jiang; Zhen Zhou; Jin-Yan Wang; Wen-Jia Guan; Lei-Gang Han; Xian-Biao Lin; Guang-Chao Zhuang (Frontiers in Marine Science, 2024)
Compounds containing one carbon atom or no carbon-carbon bond (C1 compounds), such as trimethylamine and methanol, are important climate relevant gases in the atmosphere and play key roles in global warming. The ocean is a significant source or sink of such compounds, while the concentrations of trimethylamine and methanol in seawater remain largely unconstrained due to the analytical challenges involved. Therefore, it is necessary to establish a continuous, rapid and sensitive method for the determination of these compounds with high polarity, volatility or solubility at low seawater concentrations. Here we developed a purge and trap system, coupled to a gas chromatography equipped with dual nitrogen phosphorus detector (NPD) and flame ionization detector (FID) for the simultaneous online analysis of trimethylamine and methanol at nanomolar range using a small sample volume (~ 10 mL). The dual detection of trimethylamine and methanol with NPD or FID was achieved by installing a capillary flow splitter between the capillary column and detectors. After modification and optimization of the setup and conditions, excellent linearity (R 2 > 0.99) and repeatability (< 6%) were obtained for both compounds; the detection limits for trimethylamine and methanol were 0.3 nM and 17.6 nM, respectively. Using this method, water samples collected from coastal and open ocean were analyzed; trimethylamine and methanol concentrations ranged from 0.6 to 18.8 nM and 26.0 to 256.2 nM, respectively. Collectively, this method allowed for online, rapid, sensitive and simultaneous quantification of trace trimethylamine and methanol concentrations with low-cost instrumentation and small sample volume, which makes it promising for further application in volatile compounds analysis in marine environments.

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

A ratiometric fluorescent probe based on the FRET platform for the detection of sulfur dioxide derivatives and viscosity - Feng-Ting Liu; Peng-Fei Jiang; Yan-Pu Wang; Bao-Xiang Zhao; Zhao-Min Lin (Analytica Chimica Acta, 2024)

Evaluating nutrient limitation in co-culture of Chlorella pyrenoidosa and Rhodobacter sphaeroides - Xiao-Fei Shen; Ya-Ping Xu; Yi-Fan Jiang; Lin-Jun Gao; Xiao-Qin Tong; Jing Gong; Yan-Fang Yang; Raymond Jianxiong Zeng (Science of The Total Environment, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Face-to-face conducting mechanism enabled by Si-C bonds for binder free Si@CNTs electrode - Zhi Yong Zhang; Zhe Fei Sun; Yan Liu; Bing Sheng Liu; Lin Shan Luo; Peng Fei Su; Chao Fei Lan; Shi Sheng Guo; Zi Qi Zhang; Xiang Han; Wei Huang; Zi Ping Wu; et al. (Chemical Engineering Journal, 2023)

Current Fungal Taxonomy and Developments in the Identification System - Pei Lin; MooChang Kook; Tae-Hoo Yi; Zheng-Fei Yan (Current Microbiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Complete genome sequence of Paris polyphylla chlorotic mottle virus infecting Paris polyphylla var. yunnanensis in southwest China - Qiongji He; Binghua Chen; Hongying Zheng; Yuhao Cao; Mengyin Hua; Yueyan Yin; Jiejun Peng; Junmin Li; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2023)

Differential treatment for time and frequency dimensions in mel-spectrograms: An efficient 3D Spectrogram network for underwater acoustic target classification - Ning Tang; Fei Zhou; Yan Wang; Hao Zhang; Tingting Lyu; Zhen Wang; Lin Chang (Ocean Engineering, 2023)

Complete genome sequence of a novel mitovirus detected in Colocasia esculenta - Mengting Wu; Chanchan Huang; Lin Wang; Bin Ke; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; Fei Yan (Archives of Virology, 2023)

The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2023)

Corrigendum to ‘Maternal circadian disruption before pregnancy impairs the ovarian function of female offspring in mice’ [Sci Total Environ. 2023 Mar 15;864:161161] - Yajie Guan; Manlin Xu; Zhe Zhang; Chuanming Liu; Jidong Zhou; Fei Lin; Junshun Fang; Yang Zhang; Qiuling Yue; Xin Zhen; Guijun Yan; Haixiang Sun; et al. (Science of The Total Environment, 2023)

Targeted isolation of ursane-type triterpenoids from Tragopogon porrifolius based on Feature-Based Molecular Networking - Hong-bing Sun; Hai-fei Zou; Bing Xia; Yu-cheng Gu; Wen-lin Wu; Yan Zhou (Phytochemistry Letters, 2023)

An optical study of the combustion and flame development of ammonia-diesel dual-fuel engine based on flame chemiluminescence - Wanchen Sun; Wenpeng Zeng; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Genan Zhu; Mengqi Jiang; Changyou Yu; Fei Wu (Fuel, 2023)

Multi-scale domain and microstructure engineering for the high-energy-storage BCZT based lead-free relaxor ferroelectric ceramics - Jiayue Song; Fei Yan; Jinfeng Lin; Guanglong Ge; Cheng Shi; Jin Qian; Yali Hao; Yongqi Wei; Wu Yao (Chemical Engineering Journal, 2023)

Amorphous/crystalline heterophase W-Zn(Ti)O for the removal of Cr(VI) and tetracycline in single and mixed pollutant systems - Jie Xiong; Hong-Yan Zeng; Chen-Fei Liu; Jin-Feng Peng; Zhuo-Lin Yang; Wan-Ying Ji (Chemical Engineering Journal, 2023)

Regime Shifts in the Damage Caused by Tropical Cyclones in the Guangdong–Hong Kong–Macao Greater Bay Area of China - Manli Zheng; Lin Mu; Wenjuan Li; Fei Wang; Yan Li (Journal of Marine Science and Engineering, 2023)
Tropical cyclones (TCs) pose a significant threat in terms of wind-induced damage and storm risk to the Guangdong–Hong Kong–Macao Greater Bay Area (GBA) of China. In this research, annual power dissipation index (PDI) and storm surge and wave destructive potential (SDP) index from June to November were used to estimate the damage caused by the TC events in the buffer zone of the GBA. The regime shifts in 1993 and 2013 were identified through the Bayesian changepoint detection in six TC datasets. The TC-induced damage during 1994–2012 (the low-damage period) was weaker than that in 1977–1993 and 2013–2020 (the high-damage periods). The intensity and size of stronger TCs are the dominant factors responsible for the interdecadal changes in the TC damage. This may be explained by the influences of sea surface temperature (SST), surface latent heat flux and mid-level relative humidity. During high-damage periods, TCs can extract more energy from the ocean, leading to increased TC intensity and larger size. Conversely, during low-damage periods, TCs undergo a decrease in energy intake, resulting in reduced TC power and smaller size. The variations in the SST are relative to the Luzon Strait transport. In addition, the reduction in TC translation speed is unfavorable for the development of TCs in low-damage periods. Further research suggested that mid-level steering flow affects the TC movement velocity. The results offer valuable insights into the variations in the TC-induced damage in the GBA.

A visual circuit related to the habenula mediates the prevention of cocaine relapse by bright light treatment - Yunwei Fu; Yan Yang; Lu Huang; Xiaodan Huang; Qian Yang; Qian Tao; Jijin Wu; Kwok-Fai So; Song Lin; Ti-Fei Yuan; Chaoran Ren (Science Bulletin, 2023)

Fabrication of a novel antioxidant emulsifier through tuning the molecular interaction between soy protein isolates and young apple polyphenols - Zhi Chao Song; Huan Zhang; Peng Fei Niu; Lin Shan Shi; Xue Yan Yang; Yong Hong Meng; Xiao Yu Wang; Tian Gong; Yu Rong Guo (Food Chemistry, 2023)

Experimental Investigation into the Tail-Slapping Motion of a Projectile with an Oblique Water-Entry Speed - Lin Lu; Cisong Gao; Fei Li; Dongxiao Zhang; Xuepu Yan; Qiang Li; Yanxiao Hu (Journal of Marine Science and Engineering, 2023)
In this study, the tail-slapping behavior of an oblique water-entry projectile is investigated through high-speed photography technology. The experimental images and data are captured, extracted and processed using a digital image processing method. The experimental repeatability is verified. By examining the formation, development and collapse process of the projectile’s cavity, this study investigates the impact of the tail-slapping motion on the cavity’s evolution. Furthermore, it examines the distinctive characteristics of both the tail-slapping cavity and the original cavity at varying initial water-entry speeds. By analyzing the formation, development and collapse process of the cavity of the projectile, the influence of the tail-slapping motion on the cavity evolution is explored. Furthermore, it examines the evolution characteristics of both the tail-slapping cavity and the original cavity under different initial water-entry speeds. The results indicate that a tail-slapping cavity is formed during the reciprocating motion of the projectile. The tail-slapping cavity fits closely with the original cavity and is finally pulled off from the surface of the original cavity to collapse. In addition, as the initial water-entry speed increases, both the maximum cross-section size of the tail-slapping cavity and the length of the original cavity gradually increase. With the increase in the number of tail-slapping motions, the speed attenuation amplitude of the projectile increases during each tail-slapping motion, the time interval between two tail-slapping motions is gradually shortened, the energy loss of the projectile correspondingly enlarges, and the speed storage capacity of the projectile decreases.

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

TMEM151A variants associated with paroxysmal kinesigenic dyskinesia - Hua lin Huang; Qing xia Zhang; Fei Huang; Xiao yan Long; Zhi Song; Bo Xiao; Guo liang Li; Cai yu Ma; Ding Liu (Human Genetics, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Carbon quantum dot fluorescent probe for labeling and imaging of stellate cell on liver frozen section below freezing point - Yan-Fei He; Kai Cheng; Zi-Tao Zhong; Xiao-Lin Hou; Chang-Zhi An; Jing Zhang; Wei Chen; Bo Liu; Jing Yuan; Yuan-Di Zhao (Analytica Chimica Acta, 2023)

A new chamigrane sesquiterpene from the rice fermentation of Antrodiella albocinnamomea - Min Guo; Ying-Zhong Liang; Xiu-Ming Cui; Lin-Jiao Shao; Yin-Fei Li; Xiao-Yan Yang (Natural Product Research, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Palladium-catalyzed Sonogashira coupling to synthesis of gem‑difluoroenynes - Lin Li; Yan Mei; Junlei Zhang; Kehan He; Fei Pan (Journal of Fluorine Chemistry, 2023)

Evolution characteristic of atmospheric black carbon particles at a coastal site in the Pearl River Delta, China - Jing Wei; Xiao-Feng Huang; Yan Peng; Xiao-Yu Lin; Zhen-Hua Lei; Li-Ming Cao; Wen-Fei Zhu; Song Guo; Ling-Yan He (Environmental Pollution, 2023)

Bona fide upcycling strategy of anhydride cured epoxy and reutilization of decomposed dual monomers into multipurpose applications - Lin Shao; Yu-Chung Chang; Baoming Zhao; Xinyan Yan; Brian J. Bliss; Ming-en Fei; Chenhao Yu; Jinwen Zhang (Chemical Engineering Journal, 2023)

Adaption of tobacco rattle virus to its solanaceous hosts is related to the codon usage bias of the hosts and that of the viral 16 K gene - Qi Lin; Yuanting Zheng; Yueyan Yin; Yi Chen; Miaomiao Li; Hongying Zheng; Jianping Chen; Fei Yan; Yuwen Lu; Shengchun Xu (European Journal of Plant Pathology, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Complete nucleotide sequence of hackberry virus A, a tentative member of the genus Waikavirus - Jiajia Weng; Mengting Wu; Zhuangxin Ye; Lin Wang; Bin Ke; Chanchan Huang; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; et al. (Archives of Virology, 2023)

A concise synthesis of marine natural product (−)-15-oxopuupehenol from (+)-sclarelide - Yun-Fei Cheng; Hui-Jing Li; Yin-Lin Zhang; Yan-Chao Wu (Natural Product Research, 2023)

Toxicological characteristics of drinking water in two large-scale municipal water supply systems of a metropolitan city in Central China - Huai-Ji Wang; Chen-Wei Peng; Xue Han; Yan Wang; Jie Zhang; Jun-Ling Liu; Meng-Xuan Zhou; Fei Tang; Ai-Lin Liu (Environmental Science and Pollution Research, 2023)

Effects of light on growth, feeding rate, digestion, and antioxidation in juvenile razor clams Sinonovacula constricta - Mengqi Zhang; Fei Kong; Bin Ma; Deshui Chen; Zhaoshou Ran; Shuonan Ma; Kai Liao; Jiayi Cao; Lin Zhang; Xiaojun Yan; Jilin Xu (Aquaculture, 2023)

Remarkable adsorption capacity of Cu2+-doped ZnAl layered double hydroxides and the calcined materials toward phosphate - Ding Ling Gao; Wei Wei Lin; Qiao Jing Lin; Fei Fei Dai; Yan Xue Xue; Jian Hua Chen; Yu Xiang Liu; Yang Huang; Qian Yang (Journal of Environmental Chemical Engineering, 2023)

Maternal circadian disruption before pregnancy impairs the ovarian function of female offspring in mice - Yajie Guan; Manlin Xu; Zhe Zhang; Chuanming Liu; Jidong Zhou; Fei Lin; Junshun Fang; Yang Zhang; Qiuling Yue; Xin Zhen; Guijun Yan; Haixiang Sun; et al. (Science of The Total Environment, 2023)

Synergistically enhanced structural, thermal and interfacial stability of K0.45MnO2 via tailoring the local structure for high-energy and high-power potassium-ion batteries - Yan Huang; Xinyuan Zhang; Hezhe Lin; Zhixuan Wei; Yi Zeng; Xin Ge; Wei Zhang; Xiaoqi Wang; Xu Jin; Ze Xiang Shen; Fei Du (Chemical Engineering Journal, 2023)

Do ectoparasites on fish gills “talk” with gut microbiota far away? - Lin Wang; Defeng Zhang; Jun Xie; Ouqin Chang; Qing Wang; Cunbin Shi; Fei Zhao; Hua Gong; Yan Ren; Najiah Musa; Kok Leong Lee; Houjun Pan (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Hydrate-based adsorption-hydration hybrid approach enhances methane storage density in ZIF-8@AC - Guodong Zhang; Zhe Liu; Daming Liu; Yan Lin; Fei Wang (Chemical Engineering Journal, 2023)

Magnetic nanopromoter enables excellent kinetic promotion and cycling performance in methane hydrate formation - Chen Chen; Haoyu Yuan; Xiaoming Wang; Na Wang; Yan Lin; Yan He; Fei Wang (Chemical Engineering Journal, 2023)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Correction to: circ-CCND1 regulates the CCND1/P53/P21 pathway through sponging miR-138-5p in valve interstitial cells to aggravate aortic valve calcification - Fei Yan; Xiang Xie; Qiang Huo; Weimin Zhang; Tingting Wu; Daniyaer Dilimulati; Lin Shi (Journal of Physiology and Biochemistry, 2022)

circ-CCND1 regulates the CCND1/P53/P21 pathway through sponging miR-138-5p in valve interstitial cells to aggravate aortic valve calcification - Fei Yan; Xiang Xie; Qiang Huo; Weimin Zhang; Tingting Wu; Daniyaer·Dilimulati; Lin Shi (Journal of Physiology and Biochemistry, 2022)

Complete genome sequence of iris potyvirus B infecting Lilium lancifolium in China - Qi Lin; Dankan Yan; Mengying Hua; Yueyan Yin; Hongying Zheng; Jianping Chen; Fei Yan; Jiejun Peng; Qiongji He; Yuwen Lu (Archives of Virology, 2022)

Bifunctional Ni@NiO catalyst supported on loofah sponge-derived carbon for electrocatalytic air oxidation of biorefractory pollutant in a coupling system - Min Sun; Xiong-Fei Tao; Sheng-Nan Tang; Jun Yu; Yan Wang; Lin-Feng Zhai (Environmental Science and Pollution Research, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Erratum to: Stratospheric Ozone-induced Cloud Radiative Effects on Antarctic Sea Ice - Yan Xia; Yongyun Hu; Jiping Liu; Yi Huang; Fei Xie; Jintai Lin (Advances in Atmospheric Sciences, 2022)
Erratum to: Xia, Y., Y. Y. Hu, J. P. Liu, Y. Huang, F. Xie, and J. T. Lin, 2020: Stratospheric ozone-induced cloud radiative effects on Antarctic sea ice. Adv. Atmos. Sci. , 37 (5), 505−514, https://doi.org/10.1007/s00376-019-8251-6 . This article has changed from access by subscription to OA.

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

Evolutionary and ecological patterns of scatter‐ and larder‐hoarding behaviours in rodents - Yongjun Zhang; Fei Yu; Xianfeng Yi; Weiwei Zhou; Rui Liu; Marcel Holyoak; Lin Cao; Mingming Zhang; Jiani Chen; Zhibin Zhang; Chuan Yan (Ecology Letters, 2022)
Scatter‐ and larder hoarding are the primary strategies of food‐hoarding animals and have important implications for plant‐animal interactions and plant recruitment. However, their origins and influencing factors have not been fully investigated across a wide range of taxa. Our systematic literature search amassed data for 183 seed‐hoarding rodent species worldwide and tested relationships of seed‐hoarding behaviours with phylogenetic signal, functional traits and environmental factors. We found that the evolution of hoarding strategies was not random in phylogeny, and scatter hoarding originated independently multiple times from larder hoarding. Rodents with higher encephalisation quotient (relative brain size), omnivorous diet (related to dependence on seeds) and inhabiting lower latitudes were disproportionately likely to scatter hoard. Despite body mass’s potential relationship with competition through food defence, it was associated with food‐hoarding strategy only in a few families. Our results show the need to study the community and ecological context of food‐hoarding behaviours.

Sterols and triterpenoids from Ganoderma lucidum and their reversal activities of tumor multidrug resistance - Min Wu; Cui-e Shen; Qiao-fa Lin; Jin-yi Zhong; Yan-fei Zhou; Ben-chen Liu; Jian-hua Xu; Zhi-qiang Zhang; Peng Li (Natural Product Research, 2022)

Climate warming promotes deterministic assembly of arbuscular mycorrhizal fungal communities - Xinyu Xu; Yunpeng Qiu; Kangcheng Zhang; Fei Yang; Mengfei Chen; Xi Luo; Xuebin Yan; Peng Wang; Yi Zhang; Huaihai Chen; Hui Guo; Lin Jiang; et al. (Global Change Biology, 2022)
Arbuscular mycorrhizal fungi (AMF) significantly contribute to plant resource acquisition and play important roles in mediating plant interactions and soil carbon (C) dynamics. However, it remains unclear how AMF communities respond to climate change. We assessed impacts of warming and precipitation alterations (30% increase or decrease) on soil AMF communities, and examined major ecological processes shaping the AMF community assemblage in a Tibetan alpine meadow. Our results showed that warming significantly increased root biomass, and available nitrogen (N) and phosphorus (P) in soil. While precipitation alterations increased AMF abundances, they did not significantly affect the composition or diversity of AMF communities. In contrast, warming altered the composition of AMF communities and reduced their Shannon–Wiener index and Pielou's evenness. In particular, warming shifted the AMF community composition in favor of Diversisporaceae over Glomeraceae, likely through its impact on soil N and P availability. In addition, AMF communities were phylogenetically random in the unwarmed control but clustered in warming plots, implying more deterministic community assembly under climate warming. Warming enhancement of root growth, N and P availability likely reduced plant C‐allocation to AMF, imposing stronger environmental filtering on AMF communities. We further proposed a conceptual framework that integrates biological and geochemical processes into a mechanistic understanding of warming and precipitation changes’ effects on AMF. Taken together, these results suggest that soil AMF communities may be more sensitive to warming than expected, highlighting the need to monitor their community structure and associated functional consequences on plant communities and soil C dynamics under the future warmer climate.

Complete genome sequence of a putative novel ilarvirus isolated from Eleocharis dulcis - Lanqing Lv; Xinyang Wu; Jiajia Weng; Yuchao Lai; Kelei Han; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; et al. (Archives of Virology, 2021)

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

Construction of an infectious full-length cDNA clone of potato aucuba mosaic virus - Buyang Chen; Qi Lin; Yueyan Yin; Liangliang Jiang; Fang Wang; Shuzhen Hu; Xinyang Wu; Fei Xu; Jiejun Peng; Hongying Zheng; Chengqi Yan; Xiaohan Mo; et al. (Archives of Virology, 2021)

Complete genome sequence of passiflora virus Y infecting passion fruit in China - Binghua Chen; Dali Wu; Hongying Zheng; Guangze Li; Yuhao Cao; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2021)

Study on characteristics of waterflooding in fractured reservoirs based on discrete fracture model - Fanle Meng; Junjian Li; Hanqiao Jiang; Lin Zhao; Linkai Li; Yan Qiao; Yu Zhou; Fei Xu (Arabian Journal of Geosciences, 2021)

Complete genome sequence of a novel foveavirus isolated from Allium sativum L. in China - Qi Luo; Shuzhen Hu; Qi Lin; Fei Xu; Jiejun Peng; Hongying Zheng; Guanwei Wu; Shaofei Rao; Jianping Chen; Yuwen Lu; Fengling Guo; Fei Yan (Archives of Virology, 2021)

Amniotic fluid mesenchymal stem cells repair mouse corneal cold injury by promoting mRNA N4-acetylcytidine modification and ETV4/JUN/CCND2 signal axis activation - Xinfeng Fei; Yuying Cai; Feng Lin; Yongyi Huang; Te Liu; Yan Liu (Human Cell, 2021)
Severe corneal injury is one of the main causes of loss of visual function. Mesenchymal stem cells (MSCs) have the ability to repair damaged cells in vivo. The present study aimed to explore whether MSCs could function as a cell therapy tool to replace traditional methods to treat corneal injury. CD44 + /CD105 + mesenchymal stem cells isolated from mouse amniotic fluid (mAF-MSCs) were injected into mice after cryoinjury to induce corneal endothelial cell injury. Histopathological assays indicated that mAF-MSCs could promote the growth of corneal epithelial cells, reduce keratitis, and repair the corneal damage caused by low temperature. cDNA microarray analysis revealed that the mAF-MSCs affected the expression patterns of mRNAs related to cell proliferation and differentiation pathways in the mice after transplantation. The results of quantitative real-time PCR and western blotting revealed that NAT12, NAT10, and the ETV4/JUN/CCND2 signaling axis were elevated significantly in the mAF-MSC-transplantation group, compared with those in the phosphate-buffered saline-treated groups. High performance liquid chromatography–mass spectroscopy results revealed that mAF-MSCs could promote mRNA N4-acetylcytidine (ac4C) modification and high expression of N -acetyltransferase in the eyeballs. RNA immunoprecipitation-PCR results showed that a specific product comprising Vegfa , Klf4 , Ccnd2 , Jun , and Etv4 mRNA specific coding region sites could be amplified using PCR from complexes formed in mAF-MSC-transplanted samples cross-linked with anti-ac4C antibodies. Thus, mouse amniotic fluid MSCs could repair the mouse corneal cold injury by promoting the ETV4/JUN/CCND2 signal axis activation and improving its stability by stimulating N4-acetylcytidine modification of their mRNAs.

Complete genome sequence of a new achyranthes virus A isolate from Achyranthes bidentata in China - Xinyang Wu; Yuchao Lai; Lanqing Lv; Kelei Han; Ziqiang Chen; Yuwen Lu; Jiejun Peng; Lin Lin; Jianping Chen; Hongying Zheng; Fei Yan (Archives of Virology, 2021)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Illumina sequencing revealed roles of microRNAs in different aluminum tolerance of two citrus species - Yang-Fei Zhou; Yan-Yu Wang; Wei-Wei Chen; Li-Song Chen; Lin-Tong Yang (Physiology and Molecular Biology of Plants, 2020)

Arthrobacter sedimenti sp. nov., isolated from river sediment in Yuantouzhu park, China - Pei Lin; Zheng-Fei Yan; Chang-Tian Li (Archives of Microbiology, 2020)

Verticillin A inhibits colon cancer cell migration and invasion by targeting c-Met - Qian-qian Liu; Xue-li Zeng; Yue-lin Guan; Jing-xin Lu; Kai Tu; Fei-yan Liu (Journal of Zhejiang University-SCIENCE B, 2020)

RETRACTED ARTICLE: A New Luminescent Zn(II) Complex: Selective Sensing of Cr2O72− and Prevention Activity Against Orthodontic Root Absorption by Suppressing Inflammatory Response - Yan-Feng Zhu; Wei-Qun Guan; Fei Lin; Wei-Hui Chen (Journal of Fluorescence, 2020)

Gastric smooth muscle cells manifest an abnormal phenotype in Parkinson’s disease rats with gastric dysmotility - Xiao-Lin Xiu; Li-Fei Zheng; Xiao-Yu Liu; Yan-Yan Fan; Jin-Xia Zhu (Cell and Tissue Research, 2020)

Luteimonas cellulosilyticus sp. nov., Cellulose-Degrading Bacterium Isolated from Soil in Changguangxi National Wetland Park, China - Pei Lin; Zheng-Fei Yan; Chang-Tian Li (Current Microbiology, 2020)

New insight into the molecular phylogeny of the genus Liparis s.l. (Orchidaceae: Malaxideae) with a new generic segregate: Blepharoglossum - Lin Li; Shih-Wen Chung; Bo Li; Song-Jun Zeng; Hai-Fei Yan; Shi-Jin Li (Plant Systematics and Evolution, 2020)
Molecular studies have shown that Liparis s.l. is polyphyletic, with the epiphytic Liparis alliance well separated from the clade representing Liparis in its restricted sense and further forming a phylogenetically heterogeneous assemblage. The generic status of Cestichis , as the key member of the epiphytic Liparis alliance, remains contentious, and the relationships between Cestichis , Stichorkis and Platystyliparis are still unclear and in need of further studies. We herein employ DNA sequence data from nuclear ITS and plastid mat K regions to clarify the generic boundaries of Cestichis and its relationship to the allied genera. Results from both Bayesian inference and maximum likelihood analysis congruently indicate that Cestichis as currently circumscribed is not monophyletic. The Blepharoglossum clade, corresponding to commonly recognized sect. Blepharoglossum , forms a monophyletic lineage closely related to the genus Oberonia instead of the core Cestichis clade. A re-evaluation of the diagnostic morphological characters reveals that this lineage represents a morphologically distinct group. Based on these results, Blepharoglossum is removed from Cestichis and elevated to generic status. Our study also sheds light on the homoplastic nature of some diagnostic morphological characters used traditionally in the taxonomy of the Malaxidinae.

Stratospheric Ozone-induced Cloud Radiative Effects on Antarctic Sea Ice - Yan Xia; Yongyun Hu; Jiping Liu; Yi Huang; Fei Xie; Jintai Lin (Advances in Atmospheric Sciences, 2020)
Recent studies demonstrate that the Antarctic Ozone Hole has important influences on Antarctic sea ice. While most of these works have focused on effects associated with atmospheric and oceanic dynamic processes caused by stratospheric ozone changes, here we show that stratospheric ozone-induced cloud radiative effects also play important roles in causing changes in Antarctic sea ice. Our simulations demonstrate that the recovery of the Antarctic Ozone Hole causes decreases in clouds over Southern Hemisphere (SH) high latitudes and increases in clouds over the SH extratropics. The decrease in clouds leads to a reduction in downward infrared radiation, especially in austral autumn. This results in cooling of the Southern Ocean surface and increasing Antarctic sea ice. Surface cooling also involves ice-albedo feedback. Increasing sea ice reflects solar radiation and causes further cooling and more increases in Antarctic sea ice.

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

(±)-Quassidine K, a pair of cytotoxic bis- β -carboline alkaloid enantiomers from Picrasma quassioides - Xin-Ming Guo; Fei Li; Fang-Fang Zheng; Na-Na Gong; Yan Li; Wen-Zhou Feng; Lin Tian (Natural Product Research, 2020)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Age- and Nicotine-Associated Gene Expression Changes in the Hippocampus of APP/PS1 Mice - Jie Yang; Yan Long; De-Mei Xu; Bing-Lin Zhu; Xiao-Juan Deng; Zhen Yan; Fei Sun; Guo-Jun Chen (Journal of Molecular Neuroscience, 2019)

Chronology of coastal aeolian deposition and its paleoenvironmental implications on the Liuao Peninsula of South China - Jian-hui Jin; Zhi-zhong Li; Zhi-yong Ling; Fei Zheng; Xiao-lin Xu; Yan Cheng; Xiang-dong Cao; Zhi-xing Li; Wen-jing Zhang; Yong-qing Ren (Journal of Mountain Science, 2019)

Dynamic expressions of hypothalamic genes regulate seasonal breeding in a natural rodent population - Dawei Wang; Ning Li; Lin Tian; Fei Ren; Zhengguang Li; Yan Chen; Lan Liu; Xiangfa Hu; Xuechang Zhang; Ying Song; Roelof A. Hut; Xiao‐Hui Liu (Molecular Ecology, 2019)
Seasonal breeding is a universal reproductive strategy in many animals. Hypothalamic genes, especially type 2 and 3 iodothyronine deiodinases ( Dio2 / 3 ), RFamide‐related peptide 3 ( Rfrp‐3 ), kisspeptin ( Kiss‐1 ) and gonadotropin‐releasing hormone ( GnRH ), are involved in a photoperiodic pathway that encodes seasonal signals from day length in many vertebrate species. However, the seasonal expression patterns of these genes in wild mammals are less studied. Here, we present a four‐year field investigation to reveal seasonal rhythm and age‐dependent reproductive activity in male Brandt's voles ( Lasiopodomys brandtii ) and to detect relationships among seasonal expression profiles of hypothalamic genes, testicular activity, age and annual day length. From breeding season (April) to nonbreeding season (October), adult male voles displayed a synchronous peak in gonadal activity with annual day length around summer solstice, which was jointly caused by age structure shifts and age‐dependent gonadal development patterns. Overwintered males maintained reproductive activity until late in the breeding season, whereas most newborn males terminated gonadal development completely, except for a minority of males born early in spring. Consistently, the synchronous and opposite expression profiles of Dio2/3 suggest their central function to decode photoperiodic signals and to predict the onset of the nonbreeding season. Moreover, changes in Dio2/3 signals may guide the actions of Kiss‐1 and Rfrp‐3 to regulate the age‐dependent divergence of reproductive strategy in wild Brandt's vole. Our results provide evidence on how hypothalamic photoperiod genes regulate seasonal breeding in a natural rodent population.

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Interhemispheric functional connectivity for Alzheimer’s disease and amnestic mild cognitive impairment based on the triple network model - Zheng-luan Liao; Yun-fei Tan; Ya-ju Qiu; Jun-peng Zhu; Yan Chen; Si-si Lin; Ming-hao Wu; Yan-ping Mao; Jiao-jiao Hu; Zhong-xiang Ding; En-yan Yu (Journal of Zhejiang University-SCIENCE B, 2018)

Scopulibacillus cellulosilyticus sp. nov., a cellulose-degrading bacterium isolated from tea - Zheng-Fei Yan; Pei Lin; Chang-Tian Li; MooChang Kook; Tae-Hoo Yi (Antonie van Leeuwenhoek, 2018)

Nibribacter flagellatus sp. nov., isolated from rhizosphere of Hibiscus syriacus and emended description of the genus Nibribacter - Pei Lin; Zheng-Fei Yan; Chang-Tian Li; MooChang Kook; Tae-Hoo Yi (Antonie van Leeuwenhoek, 2018)

Paracoccus pueri sp. nov., isolated from Pu’er tea - Yu-Shuai Wang; Zheng-Fei Yan; Pei Lin; Wei Gao; Tae-Hoo Yi (Antonie van Leeuwenhoek, 2018)

A new antiviral pregnane from a gorgonian-derived Cladosporium sp. fungus - Mei-Lin Yu; Fei-Fei Guan; Fei Cao; Yan-Lai Jia; Chang-Yun Wang (Natural Product Research, 2018)

Effects of different initial pH and irradiance levels on cyanobacterial colonies from Lake Taihu, China - Fei Fang; Yan Gao; Lin Gan; Xiaoyun He; Liuyan Yang (Journal of Applied Phycology, 2018)

Sucrose is involved in the regulation of iron deficiency responses in rice (Oryza sativa L.) - Peng-Fei Chen; Lin Chen; Zheng-Rong Jiang; Gao-Peng Wang; Shao-Hua Wang; Yan-Feng Ding (Plant Cell Reports, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Chemical composition and antioxidant activities of essential oils from different parts of the oregano - Fei Han; Guang-qiang Ma; Ming Yang; Li Yan; Wei Xiong; Ji-cheng Shu; Zhi-dong Zhao; Han-lin Xu (Journal of Zhejiang University-SCIENCE B, 2017)

Equisetum cf. oppositum (Equisetaceae) from the Paleocene-Eocene of Tibet in southwestern China and its paleoenvironmental implications - Guo-Lin Yang; Zi-Xi Wang; Jing-Wei Chen; De-Fei Yan; Bai-Nian Sun (Arabian Journal of Geosciences, 2016)

Trabala Vishnou Gigantina Yang (Lepidoptera: Lasiocampidae) Larval Fitness on six Sympatric Plant Species in Sea-Buckthorn Forest - Dong-Mei Wen; Lin-Feng Yu; Yong-Hua Liu; Xiong-Fei Yan; Peng-Fei Lu; You-Qing Luo (Journal of Insect Behavior, 2016)

Aeromicrobium halotolerans sp. nov., isolated from desert soil sample - Zheng-Fei Yan; Pei Lin; Xiao Chu; MooChang Kook; Chang-Tian Li; Tae-Hoo Yi (Archives of Microbiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Durability of reactive magnesia-activated slag-stabilized low plasticity clay subjected to drying–wetting cycle - Yan-Jun Du; Yu-Lin Bo; Fei Jin; Chen-Yang Liu (European Journal of Environmental and Civil Engineering, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Development of an agroinoculation system for full-length and GFP-tagged cDNA clones of cucumber green mottle mosaic virus - Hongying Zheng; Caili Xiao; Kelei Han; Jiejun Peng; Lin Lin; Yuwen Lu; Li Xie; Xiaohua Wu; Pei Xu; Guojing Li; Jianping Chen; Fei Yan (Archives of Virology, 2015)

Influence of organic and inorganic flocculants on the formation of PCDD/Fs during sewage sludge incineration - Xiaoqing Lin; Xiaodong Li; Shengyong Lu; Fei Wang; Tong Chen; Jianhua Yan (Environmental Science and Pollution Research, 2015)

Detection of pepper mild mottle virus in pepper sauce in China - Jiejun Peng; Bingbin Shi; Hongying Zheng; Yuwen Lu; Lin Lin; Tong Jiang; Jianping Chen; Fei Yan (Archives of Virology, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Observed features of temperature, salinity and current in central Chukchi Sea during the summer of 2012 - Yan He; Na Liu; Hongxia Chen; Fei Teng; Lina Lin; Huiwu Wang (Acta Oceanologica Sinica, 2015)

Functional analysis of OsPGIP1 in rice sheath blight resistance - Rui Wang; Liaoxun Lu; Xuebiao Pan; Zongliang Hu; Fei Ling; Yan Yan; Yemao Liu; Yongjun Lin (Plant Molecular Biology, 2015)

Functional relevance for multiple sclerosis-associated genetic variants - Xiang Lin; Fei-Yan Deng; Xing-Bo Mo; Long-Fei Wu; Shu-Feng Lei (Immunogenetics, 2015)

Genetic manipulation of a transcription-regulating sequence of porcine reproductive and respiratory syndrome virus reveals key nucleotides determining its activity - Haihong Zheng; Keyu Zhang; Xing-Quan Zhu; Changlong Liu; Jiaqi Lu; Fei Gao; Yan Zhou; Hao Zheng; Tao Lin; Liwei Li; Guangzhi Tong; Zuzhang Wei; et al. (Archives of Virology, 2014)

Mapping daily temperature and precipitation in the Qilian Mountains of northwest China - Shou-zhang Peng; Chuan-yan Zhao; Xiao-ping Wang; Zhong-lin Xu; Xing-ming Liu; Hu Hao; Shi-fei Yang (Journal of Mountain Science, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Overexpression of StNHX1, a Novel Vacuolar Na+/H+ antiporter gene from Solanum torvum, enhances salt tolerance in transgenic vegetable soybean - Guo-Hu Chen; Wen Yan; Li-Fei Yang; Jun-Yi Gai; Yue-Lin Zhu (Horticulture, Environment, and Biotechnology, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

Evaluation of the sedative and hypnotic effects of Eucommiol in Eucommia - Xin Li; Wenxue Zhu; Lipeng Yang; Dongqing Fei; Jinling Fan; Lin Du; Yan Liu (Natural Product Research, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Oxidative stress and MAPK involved into ATF2 expression in immortalized human urothelial cells treated by arsenic - Shengnan Liu; Fei Wang; Ling Yan; Lin Zhang; Yingli Song; Shuhua Xi; Jing Jia; Guifan Sun (Archives of Toxicology, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Be careful! Avoiding duplication: a case study - Yue-hong Helen Zhang; Xiao-yan Jia; Han-feng Lin; Xu-fei Tan (Journal of Zhejiang University-SCIENCE B, 2013)

Genetic diversity of Bartonella quintana in macaques suggests zoonotic origin of trench fever - Hao Li; Jie‐Ying Bai; Li‐Yuan Wang; Lin Zeng; Yan‐Sheng Shi; Zheng‐Liang Qiu; Hua‐Hu Ye; Xiao‐Fei Zhang; Qing‐Bin Lu; Michael Kosoy; Wei Liu; Wu‐Chun Cao (Molecular Ecology, 2013)
Bartonella quintana is a bacterium that causes a broad spectrum of diseases in humans including trench fever. Humans were previously considered to be the primary, if not the only, reservoir hosts for B. quintana . To identify the animal reservoir and extend our understanding of the ecological and evolutionary history of B. quintana , we examined blood samples from macaques and performed multilocus sequence typing ( MLST ) analysis. We demonstrated the prevalence of B. quintana infection was common in macaques from main primate centres in mainland C hina. Overall, 18.0% (59/328) of rhesus macaques and 12.7% (39/308) of cynomolgus macaques were found to be infected with B. quintana by blood culture and/or polymerase chain reaction. The infection was more frequently identified in juvenile and young monkeys compared with adult animals. In contrast with the relatively low level of sequence divergence of B. quintana reported in humans, our investigation revealed much higher genetic diversity in nonhuman primates. We identified 44 new nucleotide variable sites and 14 novel sequence types (STs) among the B. quintana isolates by MLST analysis. Some STs were found only in cynomolgus macaques, while some others were detected only in rhesus macaques, suggesting evidence of host‐cospeciation, which were further confirmed by phylogenetic analysis and Splits decomposition analysis. Our findings suggest that trench fever may primarily be a zoonotic disease with macaques as the natural hosts.

Lack of effect of continuous glycyrrhizin administration on the pharmacokinetics of the P-glycoprotein substrate talinolol in healthy volunteers - Miao Yan; Ping-Fei Fang; Huan-De Li; Ping Xu; Yi-Ping Liu; Feng Wang; Hua-Lin Cai; Qin-You Tan (European Journal of Clinical Pharmacology, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

The influence of chronic fluorosis on mitochondrial dynamics morphology and distribution in cortical neurons of the rat brain - Di-Dong Lou; Zhi-Zhong Guan; Yan-Jie Liu; Yan-Fei Liu; Kai-Lin Zhang; Ji-Gang Pan; Jin-Jing Pei (Archives of Toxicology, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

Overexpression of microRNA-378 attenuates ischemia-induced apoptosis by inhibiting caspase-3 expression in cardiac myocytes - Ji Fang; Xiao-Wei Song; Jing Tian; Hu-Yan Chen; Dong-Feng Li; Jian-Fei Wang; An-Jing Ren; Wen-Jun Yuan; Li Lin (Apoptosis, 2012)

Intron retention and 3′-UTR analysis of Arabidopsis Dicer-like 2 transcripts - Qiongji He; Jiejun Peng; Fei Yan; Lin Lin; Yuwen Lu; Hongying Zheng; Hairu Chen; Jianping Chen (Molecular Biology Reports, 2012)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

Historical and botanical evidence of distribution, cultivation and utilization of Linum usitatissimum L. (flax) in China - Fei-Hu Liu; Xia Chen; Bo Long; Rui-Yan Shuai; Chun-Lin Long (Vegetation History and Archaeobotany, 2011)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

Hepatitis B virus X protein enhances activation of nuclear factor κB through interaction with valosin-containing protein - Bo-Yan Jiao; Wan-Song Lin; Fei-Fei She; Wan-Nan Chen; Xu Lin (Archives of Virology, 2011)

Interaction between potyvirus P3 and ribulose-1,5-bisphosphate carboxylase/oxygenase (RubisCO) of host plants - Lin Lin; Zhaopeng Luo; Fei Yan; Yuwen Lu; Hongying Zheng; Jianping Chen (Virus Genes, 2011)

Mapping the self-interacting domains of TuMV HC-Pro and the subcellular localization of the protein - Hongying Zheng; Fei Yan; Yuwen Lu; Liying Sun; Lin Lin; Li Cai; Mingsheng Hou; Jianping Chen (Virus Genes, 2011)

The effect of depression on the thermal nociceptive thresholds in rats with spontaneous pain - Yuan-Lin Su; Ning Wang; Ge Gao; Jin-Yan Wang; Fei Luo (Neuroscience Bulletin, 2010)

Overexpression of PPARγ can down-regulate Skp2 expression in MDA-MB-231 breast tumor cells - Jie Meng; Yun Ding; Aiguo Shen; Meijuan Yan; Fei He; Huoyan Ji; Lin Zou; Yonghua Liu; You Wang; Xiaowei Lu; Huimin Wang (Molecular and Cellular Biochemistry, 2010)

Expression Pattern and Prokaryotic Expression for Peking Duck Insulin-Like Growth Factor-I in Escherichia coli - Yan Wu; Xiao-lin Liu; Hong-wei Xiao; Jie Wang; Fei Jiang; Sheng Zhao; Yu Liu (Biochemical Genetics, 2009)

Molecular cloning and characterization of the Dicer-like 2 gene from Brassica rapa - Fei Yan; Jiejun Peng; Yuwen Lu; Lin Lin; Hongying Zheng; Hairu Chen; Jianping Chen; Michael J. Adams (Molecular Biology Reports, 2009)

Identification of novel splice variants of the Arabidopsis DCL2 gene - Fei Yan; Jiejun Peng; Yuwen Lu; Lin Lin; Hongying Zheng; Hairu Chen; Jianping Chen; Michael J. Adams (Plant Cell Reports, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Occurrence of Fumonisin B1 in Corn from the Main Corn-Producing Areas of China - Hui-Zhi Gong; Rong Ji; Yan-Xi Li; Hong-Yu Zhang; Bing Li; Yue Zhao; Lin Sun; Fei Yu; Jun Yang (Mycopathologia, 2009)

Solid Substrate–Room Temperature Phosphorimetry for the Determination of Trace Terbutaline Sulfate Based on Its Inhibition Oxidation of Rhodamine 6G by Sodium Periodate - Jia-Ming Liu; Fei Gao; Wen-Yan Gao; Li-Qing Zeng; Xiao-Mei Huang; Zhi-Ming Li; Xiu-Chai Huang; Wei-Nv Lin; Fang-Mei Wang; Chang-Ling Nie (Journal of Fluorescence, 2008)